What lies beyond 100 years of insulin - Kirsty M. Hooper (Disease Models & Mechanisms, 2021)
It has been 100 years since the discovery of insulin. This revolutionary treatment saves the lives of millions of people living with diabetes, but much remains to be understood of its mechanisms and roles in homeostasis and disease. To celebrate this centenary, we explore areas of ongoing insulin research in diabetes, metabolic syndrome and beyond. Disease Models & Mechanisms aims to publish high-quality basic and pre-clinical research that advances our understanding of these conditions to facilitate clinical and public health impact.